Antifa’s Political Violence on Twitter: a Grounded Theory Approach - Jaccoud, Lachlan (European journal on criminal policy and research, 2023)
This paper explores antifa activists’ use of doxing on Twitter against individuals perceived as alt-right militants. Following the principles of Grounded Theory, we collected 4690 tweets published by antifa users between September 2019 and September 2020 and analysed a random subsample of 1638. Results show that antifa users perceive alt-right activists as a serious threat to their worldview and seek to neutralise their activism even at the cost of making them social pariahs. To achieve that goal, antifa activists collect personal data on persons they suspect of being alt-right activists to "build a case" and then disseminate that information through different virtual social networks to the largest audience possible. The aim of doxing is to encourage other social actors to react and take actions that could be detrimental to the individual targeted. The article discusses practical and ethical implications of this kind of political-based harassment and suggests that future research on doxing could focus on antifa blogs and websites, which include sensitive information forbidden on Twitter.